2016
DOI: 10.1126/science.aaf4332
|View full text |Cite
|
Sign up to set email alerts
|

The geomorphology of Ceres

Abstract: Analysis of Dawn spacecraft Framing Camera image data allows evaluation of the topography and geomorphology of features on the surface of Ceres. The dwarf planet is dominated by numerous craters, but other features are also common. Linear structures include both those associated with impact craters and those that do not appear to have any correlation to an impact event. Abundant lobate flows are identified, and numerous domical features are found at a range of scales. Features suggestive of near-surface ice, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 48 publications
2
73
0
Order By: Relevance
“…The dwarf planet Ceres, orbited by the Dawn spacecraft since 2015, shows a variety of different impact craters of various ages, sizes, and morphology (Buczkowski et al, ; Hiesinger et al, ). Despite previous assumptions about an upper ice‐rich mantle (Castillo‐Rogez & McCord, ), Dawn showed that many of Ceres' craters are not viscously relaxed (Bland et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dwarf planet Ceres, orbited by the Dawn spacecraft since 2015, shows a variety of different impact craters of various ages, sizes, and morphology (Buczkowski et al, ; Hiesinger et al, ). Despite previous assumptions about an upper ice‐rich mantle (Castillo‐Rogez & McCord, ), Dawn showed that many of Ceres' craters are not viscously relaxed (Bland et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Another indicator of Ceres' shallow composition is prominent fracturing of the surface, which is mostly associated with the southern craters Yalode and Uvara (Buczkowski et al, ; Crown et al, ). North of these craters, linear structures are evident as pit crater chains, grooves, or troughs, which extend in a quasi‐radial pattern northwest of Uvara crater and reach lengths of up to 143 km (Crown et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling the shape of elastically flexed topography allows for the estimation of the elastic thickness of the mechanical layer being faulted. Despite a plethora of evidence suggesting Ceres' upper layer is rich in water ice (e.g., Buczkowski et al, 2016;Combe et al, 2016Combe et al, , 2019Fu et al, 2017; Estimates of these parameters through the analysis of flexurally supported topography have previously been done on the Earth (e.g., Kusznir et al, 1991;Lowry & Smith, 1994;Weissel & Karner, 1989), Venus, (e.g., O'Rourke & Smrekar, 2018), Mars (e.g., Grott et al, 2005;Ruiz et al, 2006), Ganymede (Nimmo & Pappalardo, 2004;Nimmo et al, 2002), Europa (Nimmo & Schenk, 2006;Ruiz, 2005), Tethys (Giese et al, 2007), and Enceladus (Giese et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Dantu and Ikapati contain the largest examples of pitted terrains on the surface. Occator, Azacca, Gaue, Dantu, Haulani, and Ikapati contain fractures on their floor that are morphologically similar to class I lunar FloorFractured Craters (FFCs), whose formation is attributed to doming resulting from magmatic intrusion ( Schultz, 1976 ;Jozwiak et al, 2012 ;Buczkowski et al, 2016 ).…”
Section: Characteristics Of Craters With Floor Faculaementioning
confidence: 99%